BRANCH PRODUCTIVITY ANALYSIS OF KGB AND KVGB – A COMPARATIVE STUDY - Miriyam, Venkatanarayana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Regional Rural Banks (RRBs) are hybrid financial institutions established to cater the financial needs of rural exodus.According to the preamble of the RRBs Act of 1976, the objectives were "to develop the rural economy by providing financial assistance for the purpose of development of agriculture, trade commerce, industry, and other productive activities in rural areas, particularly to small and marginal farmers, agricultural labourers, artisans, and small entrepreneurs, and for matter connected therewith and incidental thereto”. Following India’s financial sector reforms, several changes have occurred in the focus and operation of Regional Rural Banks, and numerous efforts have been taken by the government to strengthen the commercial sustainability of RRBs.The aim of the present study is to conduct a comprehensive branch productivity analysis of Regional Rural Banks (RRBs) operating within the state of Karnataka over a five-year period, spanning from 2018-19 to 2022-23. By examining the productivity metrics and performance indicators of RRB branches during this timeframe, the study seeks to gain insights into the efficiency, effectiveness, and contribution of these institutions to rural development and financial inclusion in Karnataka.